Castaneroxy A From the Leaves of Castanea sativa Inhibits Virulence in Staphylococcus aureus - Salam, Akram M.; Porras, Gina; Cho, Young-Saeng K.; Brown, Morgan M.; Risener, Caitlin J.; Marquez, Lewis; Lyles, James T.; Bacsa, John; Horswill, Alexander R.; Quave, Cassandra L. (Frontiers in Pharmacology, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) represents one of the most serious infectious disease concerns worldwide, with the CDC labeling it a “serious threat” in 2019. The current arsenal of antibiotics works by targeting bacterial growth and survival, which exerts great selective pressure for the development of resistance. The development of novel anti-infectives that inhibit quorum sensing and thus virulence in MRSA has been recurrently proposed as a promising therapeutic approach. In a follow-up of a study examining the MRSA quorum sensing inhibitory activity of extracts of Italian plants used in local traditional medicine, 224C-F2 was reported as a bioactive fraction of a Castanea sativa (European chestnut) leaf extract. The fraction demonstrated high activity in vitro and effective attenuation of MRSA pathogenicity in a mouse model of skin infection. Through further bioassay-guided fractionation using reverse-phase high performance liquid chromatography, a novel hydroperoxy cycloartane triterpenoid, castaneroxy A (1), was isolated. Its structure was established by nuclear magnetic resonance, mass spectrometry and X-ray diffraction analyses. Isomers of 1 were also detected in an adjacent fraction. In a series of assays assessing inhibition of markers of MRSA virulence, 1 exerted activities in the low micromolar range. It inhibited agr::P3 activation (IC50 = 15.86 µM), δ-toxin production (IC50 = 31.72 µM in NRS385), supernatant cytotoxicity to HaCaT human keratinocytes (IC50 = 7.93 µM in NRS385), and rabbit erythrocyte hemolytic activity (IC50 = 7.93 µM in LAC). Compound 1 did not inhibit biofilm production, and at high concentrations it exerted cytotoxicity against human keratinocytes greater than that of 224C-F2. Finally, 1 reduced dermonecrosis in a murine in vivo model of MRSA infection. The results establish 1 as a promising antivirulence candidate for development against MRSA.